Wittgensteinian Fideism and Theology - Ommen, Thomas B. (Horizons, 1980)
An important critique of a "public" model of theological discourse has appeared in the work of a group of thinkers in the analytic tradition sometimes called "Wittgensteinian Fideists." This paper explores the model of theology representative of the Wittgensteinian Fideists, particularly that found in the work of D. Z. Phillips and Paul Holmer. Three themes are examined: the relationship between theology and ordinary language, the role of faith in theology, and the justification of theological claims. Each theme is then summarized and critically assessed in an effort to show the limitations in the Wittgensteinian model of theology and some of the ways in which an understanding of theological method can be carried beyond the point where the Wittgensteinian Fideists leave it.